2007
DOI: 10.1007/s00068-007-6210-x
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Recombinant Activated Factor VII as Adjunctive Therapy for Bleeding Control in Severely Injured Trauma Patients in Germany

Abstract: Based on preliminary evidence from a phase II trial, we conclude that, relative to placebo, rFVIIa may be a cost-effective therapy from the thirdparty payer perspective in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Figure 2 shows that 21 studies (60.0%) evaluated health care programs such as disease management programs which were assessed in 8 studies (22.9%) alone [ 21 , 25 27 , 37 , 39 , 43 , 49 ]. Evaluations were also performed on pharmaceuticals in 8 studies (22.8%) [ 30 , 35 , 41 , 44 48 ] and medical products or procedures in 6 studies (17.1%) [ 2 , 3 , 23 , 24 , 36 , 50 ]. Funding can mainly be ascribed to industry ( n = 15, 42.9%) – generally the involved health insurance fund or product manufacturer – or public sources ( n = 8, 22.9%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2 shows that 21 studies (60.0%) evaluated health care programs such as disease management programs which were assessed in 8 studies (22.9%) alone [ 21 , 25 27 , 37 , 39 , 43 , 49 ]. Evaluations were also performed on pharmaceuticals in 8 studies (22.8%) [ 30 , 35 , 41 , 44 48 ] and medical products or procedures in 6 studies (17.1%) [ 2 , 3 , 23 , 24 , 36 , 50 ]. Funding can mainly be ascribed to industry ( n = 15, 42.9%) – generally the involved health insurance fund or product manufacturer – or public sources ( n = 8, 22.9%).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the study design of the identified economic evaluations, no study used monetary values to measure effects and can therefore be classified as a cost-benefit analysis. Two studies (5.7%) measured health benefits in quality-adjusted life years (QALY) as well as life years gained and are categorized here as cost-utility analysis [ 41 , 44 ]. A total of 13 studies (37.1%) are cost-effectiveness analysis as they measured consequences in natural units such as life years gained [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 It is commonly used in cost effectiveness analyses to calculate qualityadjusted life years 14 and consists of five dimensions that assess mobility, self-care, usual activities, pain, and anxiety or depression. Each dimension is scored based on three levels of severity (no problems, moderate problems, and extreme problems).…”
Section: Hrqol Assessmentmentioning
confidence: 99%
“…The most commonly applied instruments were the SF-36 and EQ-5D; both are so-called generic instruments, suitable for assessing HRQoL in a broad range of patient populations. Of these instruments, the validity is well recognized [102][103][104][105][106][107], leading to extensive use in trauma populations for baseline and follow up assessment of HRQoL; available country specific population norms for all subscales make meaningful comparisons possible. The TOP, QOLIBRI, HASPOC, T-QoL and St. George's Respiratory Questionnaire were the only disease-specific instruments that were used in the included articles, the first four assessing specifically the impact of trauma on HRQoL.…”
Section: Summary Of Main Resultsmentioning
confidence: 99%